Response to salinity in rice: Comparative effects of osmotic and ionic stresses - Castillo, Ernesto G.; Tuong, To Phuc; Ismail, Abdelbagi; Inubushi, Kazuyuki (Informa UK Limited, 2007)
The Effects Of The Osmotic Component Of Salt Stress On Rice Cultivar Ir64 Were Examined. Treatments Were Four Combinations Of Two Levels Of Osmotic Stress At Two Developmental Stages: Medium- And High-Level Stress Applied At The Vegetative And Reproductive Stages Using Salt (Nacl) And Polyethylene Glycol-6000 (Peg) As Sources Of Osmotic Stress. Both Peg And Nacl Reduced The Total Above Ground Biomass And Delayed Flowering And Maturity, With A Longer Delay Observed With The High-Level Stress. The Reduction In Number Of Filled Spikelets, 1,000-Grain Weight, And Hence Grain Yield Was Significantly Greater When They Were Applied During The Reproductive Stage Than During The Vegetative Stage. The Sodium Concentration In Plant Tissues Also Increased In Plants Treated With Nacl, Indicating That Besides Osmotic Stress, Plants Were Also Subjected To Ionic Stress. Treatment With Nacl Decreased The Potassium Concentration In Plant Tissues But Did Not Cause Significant Differences In Phenology, Biomass Accumulation, Yield Or N Uptake Compared With Peg. We Concluded That The Response Of Ir64 To Nacl Was Attributed To The Osmotic Component. These Findings May Be Specific To Ir64, Which Has A Medium Tolerance To Salinity Stress. Further Studies Are Needed With Longer Stress Durations To Achieve A Higher Na+ Concentration In Plant Tissues In Several Varieties With Contrasting Tolerance To Salt Stress To Further Establish The Relative Importance Of Osmotic Versus Ionic Components Of Salt Stress In Rice.